2017
DOI: 10.3390/w9090716
|View full text |Cite
|
Sign up to set email alerts
|

Bedload and Suspended Load Transport in the 140-km Reach Downstream of the Mississippi River Avulsion to the Atchafalaya River

Abstract: The Mississippi River Delta has been continuously losing land since the 1930s due to several factors, chief of which is the reduced sediment supply. A few recent studies have estimated individual components of short-term sediment transport, i.e., bedload and suspended load, separately for some locations along the Lowermost Mississippi River (LmMR, commonly considered as the last 500-km reach of the Mississippi River before entering the Gulf of Mexico). However, the combined effects of both components on the lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 53 publications
1
13
0
Order By: Relevance
“…Due to preventing the main channel of Mississippi River from suddenly changing its course (avulsion) into the Atchafalaya River [3], the first phase of the Old River Control Structure (ORCS) was completed in 1963 by the United States Army Corps of Engineers (USACE). After the completion of these structures, different studies discussed whether the ORCS blocked sediments and resulted in sediment deficiency, or stabilized the channel gradient and caused riverbed aggradation [4][5][6][7][8][9][10][11][12][13][14][15][16]. In a recent modeling study, Wang and Xu [17] found that, proportionally, more riverbed materials were carried downstream in the Mississippi mainstem than to the outflow channel.…”
Section: Study Aimsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to preventing the main channel of Mississippi River from suddenly changing its course (avulsion) into the Atchafalaya River [3], the first phase of the Old River Control Structure (ORCS) was completed in 1963 by the United States Army Corps of Engineers (USACE). After the completion of these structures, different studies discussed whether the ORCS blocked sediments and resulted in sediment deficiency, or stabilized the channel gradient and caused riverbed aggradation [4][5][6][7][8][9][10][11][12][13][14][15][16]. In a recent modeling study, Wang and Xu [17] found that, proportionally, more riverbed materials were carried downstream in the Mississippi mainstem than to the outflow channel.…”
Section: Study Aimsmentioning
confidence: 99%
“…The riverbed materials along the study area (modified from Mossa [4]). The upper graph shows downstream changes in bed material using different terms (i.e., gravel, sand, silt, clay), and the lower graph shows grain size in numbers (i.e., D 50 is the median grain size, while D 84 and D 16 are the 84th and 16th percentiles used to represent the coarse fraction, respectively).…”
Section: Study Sitementioning
confidence: 99%
“…Using experimental results, many studies have analyzed the fundamental aspects of sediment transfer in turbulent flow conditions [8]. However, they propose representing sediment flow as an induction equation to relate it to flow velocity [9][10][11][12]. Knowledge of the characteristics of internal flow is critical.…”
Section: Introductionmentioning
confidence: 99%
“…As bedload accounts for approximately 10% of the sediment transported in large alluvial rivers [16,17], we only intend to deal with the suspended sediment transport. The most important parameters and characteristics of the suspended sediment transport are suspended sediment concentration (SSC), suspended sediment load (SSL), and PSD, along with characteristic particle sizes [18].…”
Section: Introductionmentioning
confidence: 99%